Expert recommendations for Germany’s integration of psychedelic-assisted therapy - Perez Rosal, Sergio R.; La Torre, Joseph T.; Birnkammer, Susanne; Chernoloz, Olga; Williams, Monnica T.; Faber, Sonya C. (Université d'Ottawa | University of Ottawa, 2024)
Abstract As clinical trials for psychedelics move into phase III in the USA, Europe must address its lag in integrating professional education around psychedelic-assisted therapy (PAT) and supporting psychedelic drug research. This paper evaluates the necessary frameworks for implementing PAT in Germany, emphasizing the nation’s potential leadership role within the European Union. With Australia having already approved MDMA and psilocybin for mental health indications, the Ukrainian government exploring MDMA treatment for war-related PTSD, and initial clinical trials involving MDMA and LSD with patients in Switzerland which restarted the restricted medical use of these substances around 2014, the medical authorization of psychedelics in these countries establishes precedent showcasing both the promise and challenges of researching and implementing PAT in nations where the substances were formally scheduled as illicit substances. Key challenges include establishing rigorous standards for practitioner training, accessibility, and defining regulatory oversight. This paper focuses on the development of robust infrastructure in Germany, which will support the roll out of PAT, and details ethical considerations, training protocols, and governmental roles in the formulation of treatment frameworks. This approach aims not only to guide Germany in adopting PAT but also to influence broader European policy, ensuring that patients receive ethically sound and proficient care. The findings suggest pathways for Europe to reclaim its historical lead in psychiatric and therapeutic innovation.